Balancing training and outcomes in total knee replacement: A ten-year review. Issue 4 (August 2018) - Faulkner, A.; Reidy, M.J.; Davies, P.S.E.; Wang, W.; Buddhadev, N.; Johnston, L.; Clift, B.
Abstract: Introduction: 10-year study examining differences in total knee arthroplasty (TKA) functional outcomes and survivorship in patients operated on by consultant and trainee orthopaedic surgeons. Method: Data was prospectively collected from all elective TKAs performed at our three linked institutions. Patient demographics, surgeon grade, and length of hospital stay were recorded. Outcomes pre-operatively and at 1, 3, 5, 7 and 10 years included mortality, need for revision surgery and function as documented by the patients' Knee Society Score. Results: 686 patients were included in the study. 450 (65.5%) patients were operated by consultant surgeons and 236 (34.4%) by trainees. On multivariate analysis no significant differences were observed between groups in length of hospital stay (p = 0.695), implant survival (p = 0.422), and function (p = 0.507) at 10 years. On Cox regression analysis no significant difference was observed in mortality (p = 0.209) at 10 years. 4 patients over this time period were lost to formal follow up. Conclusion: No significant difference was observed in the TKA outcomes between consultants and trainees 10 years post-operatively.